Type 2 diabetes is independently associated with all-cause mortality secondary to ventricular tachyarrhythmias - Weidner, Kathrin; Behnes, Michael; Schupp, Tobias; Rusnak, Jonas; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Hoppner, Jorge; El-Battrawy, Ibrahim; et al. (Cardiovascular diabetology, 2018)
The study sought to assess the prognostic impact of type 2 diabetes in patients presenting with ventricular tachyarrhythmias on admission.